Effects of nano mineral-supplemented diet on sow productivity - Son, Hoang Nghia (Academia Journal of Biology, 2019)
This study aimed to evaluate the effects of nano mineral-supplemented diet on sow productivity. The data were estimated by several parameters consisting of piglet live ratio at newborn stage and weaning stage, piglet weight at newborn stage and weaning stage, metal content in piglet livers. The results showed that live ratio of newborn piglets in group III was highest (93.44 ± 2.83%) comparing with other groups. However, there was no significant difference of live ratio in piglets at weaning stage between nano mineral-supplemented groups with control. The birth weight of piglets in nano mineral-supplemented groups was similar to control group. The birth weight of piglets in nano mineral-supplemented groups was ranged from 1,361.61 ± 47.37 grams (group II) to 1,410.48 ± 44.28 grams (group I). However, the average weight of weaned pigs in groups III and IV was higher than other groups (6,772.92 ± 105.47 grams and 6,818.87 ± 89.59 grams). Moreover, the amount of Fe, Cu, Zn, Mn in piglet liver from nano mineral-supplemented groups have been found to be lower than those in control group. These results revealed that the supplement of nano minerals for sows promoted the reproductive performance of sows and reduced mineral content in the liver of piglets.